WHY THE AUSTRALIAN GOVERNMENT DOES NOT USE DECISION SUPPORT SYSTEMS FOR TOBACCO CONTROL AMONG ADOLESCENTS - Petrovic-Lazarevic, Sonja (The journal of contemporary issues in business and government, 2007)
The paper points to the decision support systems' application in improving the Australian Government tobacco control decision processes relevant to adolescents. Most smokers are recruited as juveniles. Once started, there is a tendency for this age group to become addicted to it (Bachman et al., 1997; QUIT, 2006). The research project findings indicate that the Australian Government tobacco control decision process may be influenced by interested groups, is not dealing with tobacco control for adolescents and is not using decision support systems. If applied, however, the theoretical contributions of decision support systems can improve tobacco control decision processes to prevent juveniles becoming smokers and decrease the high death rate caused by smoking-related illnesses.